Visceral adipose tissue and osteoarthritis, a two-sample Mendelian randomized study - Zhang, Yinzhen; Wang, Yanpeng; Xu, Ji; Wang, Zhengyan; Zhao, Wenhai; Zhao, Changwei (Frontiers in Medicine, 2024)
Background: The relationship between visceral adipose tissue and osteoarthritis is not clear. The purpose of our study was to explore the relationship between visceral adipose tissue and osteoarthritis.Methods: We used a two-sample Mendelian randomization method to select single nucleotide polymorphisms(SNPs) significantly associated with visceral adipose tissue as instrumental variables to explore the relationship between visceral adipose tissue and all osteoarthritis, hand osteoarthritis, hip osteoarthritis, knee osteoarthritis, and spine osteoarthritis. The reliability of the results was tested by sensitivity analysis.Results: Our findings indicated that visceral adipose tissue was associated with all osteoarthritis, hip osteoarthritis, knee osteoarthritis, and spine osteoarthritis (all osteoarthritis: